An integrated approach to determine three‐dimensional accretion geometries of tidal point bars: Examples from the Venice Lagoon (Italy). Issue 1 (18th September 2020) - Cosma*, Marta; Yan, Na; Colombera, Luca; Mountney, Nigel P.; D'Alpaos, Andrea; Ghinassi*, Massimiliano
Abstract: Low rates of lateral migration (centimetres to decimetres per year) combined with relatively high rates of vertical accretion (millimetres to centimetres per year) recorded in microtidal channels of the Venice Lagoon (Italy) give rise to point‐bar geometries and internal facies arrangements that differ substantially from widely accepted models of point‐bar sedimentary architecture. In this study, field data from the Venice Lagoon are combined with a three‐dimensional forward stratigraphic model, the 'Point‐Bar Sedimentary Architecture Numerical Deduction' (PB‐SAND), to predict the stratal geometries of point bars formed in aggradational settings. The PB‐SAND uses a combined geometric and stochastic modelling approach that can be constrained by field evidence. The model applied determines the geometry of four point bars generated by 9 to 11 m wide channels cutting through salt marshes. An iterative best‐fit modelling approach has been used to obtain multiple simulations for each case study, each of which fits the observations derived from the analysis of time‐series historical aerial photographs and 44 sedimentary cores. Results demonstrate how the geometry of the bars is determined by the development of two key stratal surfaces: the point‐bar brink and channel‐thalweg surfaces. These surfaces are defined by the progressive translation and vertical shift of the point‐bar brink (i.e. break of slope between bar top and bar slope) and the channel thalweg (i.e. deepest part of the channel) during bar evolution. The approach is used to: (i) reconstruct three‐dimensional point‐bar geometries; (ii) propose alternative reconstructions; (iii) provide insight to drive the acquisition of additional data to better constrain the proposed models; and (iv) provide insight into the mechanism of bar growth for slowly migrating channels in settings subject to relatively high rates of aggradation. This study highlights how interaction between styles of planform transformation and latero‐vertical shifts of meandering channels can determine the geometry of related sedimentary bodies.